An evaluation of communication barriers and facilitators at the time of a mental health diagnosis: a survey of health professional practices - Milton, A. C. (Epidemiol Psychiatr Sci, 2017)
AIMS. To examine health professionals’ views and practices relating to the specific barriers to communication that arise at the time of mental health diagnosis, and the strategies used to support individuals throughout this process. METHODS. An online survey of the beliefs and practices of 131 mental health clinicians working in different clinical settings across Australia was conducted. RESULTS. Exploratory factor analysis of the items relating to barriers to communication resulted in three latent factors (‘stigma, diagnosis and risk’; ‘service structure’; and ‘individual circumstances’ such as the person receiving the diagnosis being young, having a culturally and linguistically diverse background or being unwell at the time of conversation). Using linear regression it was found that variance in ‘stigma, diagnosis and risk’ was significantly explained by whether participating clinicians had medical training, their experience working with serious mental health problems, their confidence handling distress and attitude towards diagnosis. Variance in ‘individual circumstances’ was significantly explained by participating clinicians’ confidence handling distress. The most frequently used strategies to support diagnostic discussions centred on the health professionals’ communication skills, gauging the individual's perception of their circumstances, responding with empathy, following-up after discussion, addressing stigma concerns, using collaborative practice and setting up for the conversation. CONCLUSIONS. Three main areas for health professionals to reflect on, plan for and ultimately address when discussing news with the individual concerned emerged (‘stigma, diagnosis and risk’; ‘service structure’; and ‘individual circumstances’). Variations in practice indicate that practitioners should be cognisant of their own beliefs and background and how this impacts their communication practice.